Inflammation of Bone in Patients with Periprosthetic Joint Infections of the Knee - Lara Biedermann; Evgeniya Bandick; Yi Ren, MD; Serafeim Tsitsilonis, MD; Stefanie Donner, MD; Michael Müller, MD; Georg Duda, PhD; Carsten Perka, MD; Arne Kienzle, MD (JBJS Open Access, 2023)
Background:. Despite the general success of total knee arthroplasty (TKA), addressing periprosthetic joint infection (PJI) and the resulting long-term complications is a growing medical need given the aging population and the increasing demand for arthroplasty. A larger proportion of patients face revision surgery because of the long-term complication of aseptic loosening despite clearance of the infection. The pathomechanisms leading to prosthetic loosening are not understood as it has been widely assumed that the bone stock recovers after explantation revision surgery. While clinical observations suggest a reduced osteogenic potential in patients with PJI, knowledge regarding the relevant biology is sparse. In the present study, we investigated the inflammatory impact of PJI on the bone and bone marrow in the vicinity of the joint. Additionally, we evaluated changes in the local inflammatory environment in a 2-stage exchange at both explantation and reimplantation. Methods:. In this study, we analyzed 75 human bone and bone-marrow specimens (obtained from 65 patients undergoing revision arthroplasty with cement for the treatment of PJI) for markers of inflammation. Samples were analyzed using hematoxylin and eosin overview staining, fluorescent immunohistochemical staining, flow cytometry, and polymerase chain reaction (PCR). Results:. Leukocyte prevalence was significantly elevated at explantation (femur, +218.9%; tibia, +134.2%). While leukocyte prevalence decreased at reimplantation (femur, −49.5%; tibia, −34.2%), the number of cells remained significantly higher compared with the control group (femur, +61.2%; tibia, +54.2%). Expression of inflammatory markers interleukin (IL)-1α (femur, +2,748.7%; tibia, +1,605.9%), IL-6 (femur, +2,062.5%; tibia, +2,385.7%), IL-10 (femur, +913.7%; tibia, +897.5%), IL-12 (femur, +386.1%; tibia, +52.5%), IL-18 (femur, +805.3%; tibia, +547.7%), and tumor necrosis factor (TNF)-α (femur, +296.9%; tibia, +220.9%) was significantly elevated at prosthesis explantation in both femoral and tibial specimens. Expression remained significantly elevated at reimplantation for all inflammatory markers except IL-12 compared with the control group. Conversely, there were only limited inflammatory changes in the bone marrow environment. Conclusions:. The present study demonstrated a strong and lasting upregulation of the proinflammatory environment in the joint-surrounding osseous scaffold in patients with PJI. Our data suggest that modulating the inflammatory environment has substantial potential to improve the clinical outcome in affected patients.